Interactive web mapping tools and custom subsurface cross-sections for interdisciplinary geologic investigation. (March 2022) - Gardner Oldemeyer, Tessica Anne; Russell, Glenn Paul
Abstract: Using Python-based geospatial analytics, open-source web mapping technologies, geophysical data models, and subsurface stratigraphy models from the Regional Geology Geologic Framework Model database assembled by Los Alamos National Laboratory, we developed a suite of web-based geologic investigation tools to identify and understand subsurface structures and geophysical properties concerning salt and shale formations within the contiguous United States. Coupled with a web map interface, these tools allow for the interactive visualization of various geologic data and demonstrate the ability to quickly generate custom subsurface cross-sections, borehole charts, and diagrams for azimuthal orientation data. These capabilities were developed for stakeholder and researcher use to facilitate informed decision making for spent nuclear waste disposition. However, these capabilities provide a flexible model for a variety of subsurface investigation needs, and we have demonstrated this flexibility by adapting these tools to meet visualization needs for various subsurface models within a web-based platform. Highlights: Web-based tools provide on-demand, custom cross-sectional profiles, borehole charts, and rose diagrams for researcher use. Web map-based approach offers efficiency and accessibility for subsurface data navigation and visualization. Tools allow for interactive visualization of spatial relationships among subsurface and geophysical data. Adaptive tools can incorporate any rasterized, gridded models for subsurface structure or geophysical data. Techniques allow for the visualization of overlapping, spatially discontinuous data over various spatial extents.